A KINEMATIC ANALYSIS OF MECHANUM WHEEL WITH THE TAYLOR SERIES APPROXIMATION AT DIFFERENT ORDERS: Kinematics Analysis - Haripamyu Haripamyu; Fauzi Rahmatullah Siregar; Mahdhivan Syafwan (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2026)
The mecanum wheel is an essential component in omnidirectional robotic systems, enabling free movement in any direction without changing orientation. The complexity of its kinematics requires a mathematical model that is both accurate and efficient. This study analyzes the contact point velocity equations of a mecanum wheel by considering all velocity components, then simplifies them using first-, second-, and third-order Taylor series approximations. The model is numerically simulated for different numbers of rollers (N = 6, 8, 12) with predefined geometric and motion parameters. Simulation results show that the first-order approach produces relatively large errors, especially with fewer rollers. The second-order approach significantly reduces the Root Mean Square (RMS) error compared to the first order, while the third order provides no notable improvement over the second. Increasing the number of rollers also results in smoother and more accurate velocity curves. In conclusion, the second-order Taylor series approximation is sufficient to efficiently model mecanum wheel kinematics withhigh accuracy, making it suitable for mobile robot control applications.